‘This Just Isn't Sustainable’: Precarious Employment, Stress and Workers' Health - Clarke, Marlea; Lewchuk, Wayne; de Wolff, Alice; King, Andy (International Journal of Law and Psychiatry, 2007)
This paper explores the impact of precarious employment relationships on health outcomes. It uses a novel framework, “Employment Strain” to describe the characteristics of different employment relationships and how they impact health outcomes. It uses interview data and comments provided on a survey to explore these issues. The paper begins by exploring if the health effects reported by mid-career individuals in precarious employment are different from those of younger and older workers. Finding limited evidence to support this hypothesis, the paper goes on to explore in detail the conditions under which precarious employment does increase stress and tension and impact health outcomes. It concludes that a combination of an individual's desire for more permanent employment, the expectation that permanent employment will be found, and the support individuals receive from various sources are critical to understanding the health effects of precarious employment.
Keywords: Age; Employment strain; Gender; Health; Precarious employment; Stress; Support